Common Background Signals in Voltammograms of Crystalline Silicon Electrodes are Reversible Silica-Silicon Redox Chemistry at Highly Conductive Surface Sites - Zhang, S.; Ferrie, S.; Peiris, C.R.; Lyu, X.; Vogel, Y.B.; Darwish, Nadim; Ciampi, Simone (AMER CHEMICAL SOC, 2021)
The electrochemical reduction of bulk silica, due to its high electrical resistance, is of limited viability, namely, requiring temperatures in excess of 850 °C. By means of electrochemical and electrical measurements in atomic force microscopy, we demonstrate that at a buried interface, where silica has grown on highly conductive Si(110) crystal facets, the silica-silicon conversion becomes reversible at room temperature and accessible within a narrow potential window. We conclude that parasitic signals commonly observed in voltammograms of silicon electrodes originate from silica-silicon redox chemistry. While these findings do not remove the requirement of high temperature toward bulk silica electrochemical reduction, they redefine for silicon the potential window free from parasitic signals and, as such, significantly restrict the conditions where electroanalytical methods can be applied to the study of silicon surface reactivity.